Effects of food on the central and peripheral haemodynamic response to upright exercise in normal volunteers. - Yi, J J (1990)
The central and peripheral haemodynamic effects of a modest meal were investigated in healthy volunteers at rest and in response to submaximal exercise. The meal increased heart rate, cardiac output, oxygen consumption, carbon dioxide production, and minute ventilation at rest and during exercise. The effects of food were additive to those induced by the exercise. Food had no effect on limb blood flow and lowered total systemic vascular resistance suggesting that there were no compensatory changes in regional blood flow to help redirect blood to the gut. An increase in cardiac output, and therefore myocardial work, is the predominant cardiovascular response to eating and this may help explain the postprandial deterioration in symptoms of some patients with cardiovascular disorders.